A new model of the IO-Controlled Jovian decametric radiation - Goertz, Christoph K (Rhodes University, Faculty of Science, Department of Physics, 1972)
Jupiter, the largest planet in the solar system, is not only an emitter of thermal radiation like any other planet. Jupiter also emits relatively high-intensity non-thermal radiation in two bands, the decimetre wavelength range and the decametre wavelength range (5 MHz< f < 40 MHz). The decimetric radiation is believed to be due to synchrotron radiation of electrons trapped in a kind of Jovian "Van Allen belt". This thesis deals almost exclusively with the decametric radiation. Although the decametric radiation has been observed for 15 years since its discovery by Burke and Franklin in 1955, there is no generally accepted theoretical model of its generation to be found in the literature as yet. This is not surprising, as there are many complex and confusing aspects of the radiation. And since our knowledge of the Jovian ionosphere, magnetosphere and magnetic field is very limited indeed, every theoretical model must be based on some more or less well justified assumptions. It is, however, possible to draw some conclusions from the observed properties of the decimetric and decametric radiation. The radiation in both bands is polarized. It has been shown that at least part of the polarization is an intrinsic property of the radiation source at Jupiter, This indicates the existence of a Jovian magnetic field. The magnitude and shape of the magnetic field, however, is open to discussion, although a dipole field does seem to be a good approximation at least for large distances from Jupiter. Intro. p. 1-2.
Keywords: Jupiter (Planet); Radiation; Magnetosphere; Ionosphere